Needs Analysis of Digital Media-based Disaster Mitigation Education for Gen Z - Anindhita, Wiratri; Samadi, Samadi; Rahmawati, Devie; Ramadhoan A’rachman, Fauzi (Journal of Science and Education (JSE), 2024)
This research aims to analyze the needs of Gen Z in integrating digital media into disaster mitigation education. This research method uses a qualitative approach with a case study. The participants in this study were 16 people in Pramuka Island, Kepulauan Seribu. The selection of these participants was carried out using purposive sampling technique. In-depth interviews, observation and documentation are data collection techniques conducted by researchers. The results of this study indicate that gen Z has digital literacy competencies only limited to internet searching, and hypertextual navigation. Meanwhile, content evaluation and knowledge assembly cannot be done effectively by Gen Z due to knowledge constraints and poor internet signal. In general, Gen Z understands information related to natural disasters and the impact of natural disasters. The results of this study conclude that gen Z needs digital media that can contain information as a tool to introduce disaster mitigation education. However, the digital media can not only be accessed through the internet online, but can also be used offline. Thus, digital media-based disaster mitigation guides need to be developed in future research.